2023
DOI: 10.1093/nar/gkad184
|View full text |Cite
|
Sign up to set email alerts
|

The molecular grammar of protein disorder guiding genome-binding locations

Abstract: Intrinsically disordered regions (IDRs) direct transcription factors (TFs) towards selected genomic occurrences of their binding motif, as exemplified by budding yeast's Msn2. However, the sequence basis of IDR-directed TF binding selectivity remains unknown. To reveal this sequence grammar, we analyze the genomic localizations of >100 designed IDR mutants, each carrying up to 122 mutations within this 567-AA region. Our data points at multivalent interactions, carried by hydrophobic—mostly aliphatic—re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 89 publications
2
13
0
Order By: Relevance
“…First, activation domains (ADs) that recruit coactivators to induce gene expression reside inside such regions ( 7–14 ). Second, IDRs can complement the DBD in directing TF binding preferences along genomes ( 5 , 6 , 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, activation domains (ADs) that recruit coactivators to induce gene expression reside inside such regions ( 7–14 ). Second, IDRs can complement the DBD in directing TF binding preferences along genomes ( 5 , 6 , 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different functions were attributed to common IDR design features. For example, studying Msn2, we found that the spreading of hydrophobic residues within an otherwise disordered sequence is the key IDR-design feature underlying its role in directing binding preferences ( 16 ). Others have reported similar features defining transcription activation domains ( 10–14 ), and additional work associated these same patterns with phase separation and formation of protein condensates ( 23–25 ).…”
Section: Introductionmentioning
confidence: 99%
“…We, however, did not find a similar contribution from the negatively charged N-terminal extension. Certainly, nature has established multiple modes of fine-tuning DNA recognition through IDRs 71-73 , including roles for hydrophobic sequences as recently shown by Jonas et al 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, nature has established multiple modes of fine-tuning DNA recognition through IDRs [71][72][73] , including roles for hydrophobic sequences as recently shown by Jonas et al 74 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, these regions can harbor important functions such as mediating protein-protein interactions [21], providing structural components needed to remodel chromatin [22], modifying DNA binding [23], and facilitating cooperative interactions with other transcriptional regulators [24,25]. For any particular transcription factor, the sequence-function relationship for regions outside of the DNA binding domain is often unclear, making it difficult to predict how evolutionary changes in this region will impact transcription factor function without empirical tests [26].…”
Section: Introductionmentioning
confidence: 99%